Characterization and physicochemical properties of collagen extracted from barramundi (Lates calcarifer, block) skin - Mohamad Razali, Umi Hartina (2012)
Collagens from barramundi (Lates calcarifer) skins were extracted by alkaline pretreatment with mild acid extraction (0.5 M acetic acid); with and without (ASC) the addition of pepsin (PSC) and papain (PaSC). The use of papain was studied to replace the use of conventional enzyme, pepsin, in the collagen extraction process, which is of haram or non-halal origin. The collagens obtained were evaluated for their physico-chemical properties such as colour, odour, amino acid composition, molecular weight distribution and solubility haracteristics. Optimization for collagen extraction using papain was carried out by Response Surface Methodology (RSM). The selected independent variables were papain concentration (10-50 kUnit/g) and extraction time (12-36 hr) with dependent variables of yield,hydroxyproline, total amino acid and imino acid content. Comparisons were then carried for the collagen obtained from the optimized process with commercial mammalian and tilapia collagens in their amino acid composition, thermal stability,viscosity and isoelectric point. The microstructures of the collagens were evaluated by scanning electron microscopy (SEM) while their secondary structures were determined using Fourier Transform Infrared Spectroscopy (FTIR). Five-fold increments in yield were obtained by enzymatic extraction when compared to the non-enzymatic (8.1 %) extraction. Both PSC and PaSC produced high yields (~44 %). The protein content of the collagens was in the range of 60-85 %. The collagens were basically colourless although the enzymes aided-extractions were slightly darker. Collagens from papain treatment had the highest total amino acid content (728.54 mg/g), with pre-dominant amount of glycine,proline, alanine and arginine. Imino acid (pro+hyp) content of ASC, PSC and PaSC were 193, 198 and 195 residues/1000 residues, repectively. The SDS-PAGE pattern of PSC was similar to ASC; however, PaSC was distinctly different. All the extracted collagens were of type 1 with apparent polypeptides molecular weight distribution of 37 to 250 kDa. They had high solubility in pH of 2 to 5 and increasing NaCl concentration up to 2%. Response Surface Analysis showed the significant (p<0.05) in all reduced models with high overall coefficient of determination value (R2> 0.8). The optimized process was the combination of 30.4 kUnit/g of papain and at 24.5 hr of contact time. The predicted collagen yield, hydroxyproline, total amino acid and imino acid content under optimal conditions were estimated to be 58 %, 90 residues,935 mg/g and 214 residues, respectively. The experimental values were 59.7 %, 89 residues, 948 mg/g and 209 residues, respectively. The imino acid content of barramundi collagen was higher than the commercial bovine collagen (202), but lower than observed for porcine collagen (220). Tmax of barramundi collagen was found at 38.17 ºC. The viscosity of barramundi and commercial mammalian collagens decreased rapidly with increasing temperature from 5 to 35 °C, and then decreased at a slower rate from 40 to 50 °C. Isoelectric point (pI) of barramundi collagen determined by zeta potential was at pH 6.01. Based on the FTIR analysis,amide A, B I, II and III were detected for all collagens with slightly different IR regions.